PENGARUH MOTIVASI KERJA DAN KOMPETENSI PEGAWAI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA DEPOK TAHUN 2013 - Sangadji Sangadji (KENEGARAAN, 2016)
The research are conducted in di Dinas Kependudukan dan Pencatatan Sipil Kota Depok, because several reasons are for instance, centralize service procedure, service traits, inconvenient services, and extra-cost for issuing birth certificate. The method of research is applied quantitative with SEM analysis. The output of the research are motivation and jobperformance indirectly through job-satisfaction, influenced 0.18. Competence is indirectly influenced to job-performance through job-satisfaction within 0.10 coefficients.Keywords: Motivation, Competency, and Job Performance